The mixed and hybrid criminal courts of Brazil: Mainstreaming restoration, rehabilitation and community justice in a human rights context - Kirchengast, Tyrone (International review of victimology, 2021)
In Brazil, minor to mid-level criminal offences are dealt with through an inventive community problem-solving paradigm that sees a shift from traditional court engagement between the accused and state towards a therapeutic process that involves all participants in the justice process. This article considers the work of the Domestic Violence and Special Justice Courts of Brazil, by examining their use of a mixed and hybrid adversarial-inquisitorial criminal procedure that supports a participatory model of community and problem-solving justice in a human rights context. The article argues that this hybrid and mixed approach to criminal justice allows for the mainstreaming of problem-centred and community justice through the adoption of human rights measures that afford justice to all participants in the criminal justice process. This approach sees the forging of relationships between traditional and non-traditional justice stakeholders, specifically victims, police, the judiciary, defendants, the community and service providers, as a central rather than alternative pathway to justice. Importantly, this innovative criminal procedure as a standard response to crime provides for longer-term community building by engaging victims and the accused through a range of informal processes that support admonishment of wrongdoing and conciliation between the victim, offender and community, albeit more serious matters invariably proceed directly to trial. Lessons from this mixed and hybrid model for adversarial jurisdictions attempting to better integrate problem-solving justice follow.